Power of Positivity: Exploring the Experiences of Senior High School Teachers and its Impact to Learners - Ana Lyn T Soriano; Abraham C Soriano (ASEAN Multidisciplinary Research Journal, 2022)
This study focused on exploring the experiences of Senior High School teachers in integrating the positivity approach in their classroom and the experiences of SHS learners in these teachers’ classes. This study is qualitative in nature and used qualitative–phenomenological approach. Participants of the study included fifteen teachers who have taught in the Senior High School department of Bolinao School of Fisheries for three school years. The interview sessions were done via phone calls with the researchers as the interviewer. Meanwhile, 40 SHS learners were included as students-respondents. Questionnaires were floated and were retrieved via social media platform. The narrated stories of the teachers-participants revealed that they applied similar methods to integrate positivity approach in the classroom to ensure the provision of warmth, structure, and setting of long-term goals. The teachers felt overwhelming fulfillment, satisfaction and rewarding experiences in seeing the impact of their effort to apply positivity approach in their classes as they witnessed improved academic performances, higher levels of engagement, transformed academic and non-academic behavior of learners, the success of the students’ even beyond senior high school, and established friendships with the SHS learners. The data gathered from the learners validated the teachers’ use of positivity methods in the classroom. School administrations, in all levels, including those at the tertiary levels, must enforce and sustain a “strengthened” policy to implement and monitor the use positivity approach in classrooms.